Methods of in vitro study of galectin-glycomaterial interaction - Heine, Viktoria; Dey, Carina; Bojarová, Pavla; Křen, Vladimír; Elling, Lothar (Biotechnology advances, 2022)
Galectins are a family of carbohydrate-binding lectins modulating cell events such as cell proliferation, apoptosis, adhesion or migration by cross-linking the glycan structures of cell membranes and/or extracellular matrix components. In a diseased organism, galectins are upregulated and trigger the progression of diseases such as inflammation, cancerogenesis, fibrosis, cardiovascular and metabolic disorders. Targeting galectins with glycomaterials for the aims of diagnostics or therapy is, therefore, a focus of biotechnological and biomedicinal research, and already led to candidates for clinical trials. Testing and evaluation of galectin-glycomaterial interactions require informative and versatile analytical methods at several levels of knowledge, from basic inter-molecular interaction to complex cell-based assays. This review aims to classify and characterize a selection of the most promising methods to identify the prospective glycomaterials for translating galectin targeting from the molecular level to the level of tailored in vivo assays.
Keywords: buněčná membrána; Glycoconjugate; galektiny; Carbohydrate; Galectins; polysacharidy; apoptóza; Inflammation; prospektivní studie; Polysaccharides; Prospective Studies; Biosensor; Galectin; Cell Membrane; Apoptosis; Cancer